Autobiografie scolastiche e scelta universitaria - Enzo, Catarsi (Firenze University Press, 2006)
The transformations of our society place the onus on the teaching professions to acquire new skills to enable them to respond to the needs of a complex reality in constant evolution. This is why the Degree Course for Professional Educator has gone through ongoing radical changes over recent years, designed to synthesise the theoretical and practical dimensions. This book is aimed at recording such changes in the attempt to provide a snapshot of the youth universe through the discussion of data emerging from a questionnaire, and the analysis of various scholastic autobiographies written by the students themselves. The objective of the publication is to understand the backgrounds of our students, what are their relations with the school and with the teachers, what expectations they have in relation to the academic world and their future in professional and personal terms. The book is therefore aimed at secondary school teachers, at University teachers and at the educators themselves, as well as at all those who are engaged with young people and adolescence in various capacities.